“An absolute pillar of strength for her husband and the struggle”: Molly Fischer (1908-1964) – wife, mother and struggle activist - Hannes Haasbroek (Contree, 2012)
This article concentrates on the life and times of Molly Fischer, wife of the renowned Communist and struggle-activist Bram Fischer. Molly and Bram’s life was not only woven together by their love for each other, but also by their love of Socialism and Communism coupled with their sincere endeavours to uplift the black community. She was as fervent a Communist and activist as Bram and in these circles was applauded for the unselfish manner in which she took up the cudgels for the oppressed people in the country. Molly is probably one of the few white women in the struggle-history of South Africa who had an Afrikaans background and who made a notable contribution to this cause. Her contribution remained rather obscured to the general public when compared with that of her famous husband. Therefore, the purpose of this article is to emphasise how she played her part as a struggle-activist and how she, as her husband’s soul mate, supported him throughout his public and political life and, in the interests of their cause, never backed away from the mistrust which they were obliged to endure from their Afrikaner compatriots. Also her role as mother, and for that matter homemaker, is taken into consideration. A great deal of Molly’s everyday life centred on their son’s welfare who suffered from cystic fibrosis.